Efektivitas Video Pendek sebagai Media Pemasaran Digital: Bukti Empiris dari Konsumen Milenial dan Gen Z - Airyq, Irnin Miladdyan; Putri, Intan Meilani; Sundoro, Fredericho Mego; Aswin, Aswin (Institut Teknolog dan Bisnis Diniyyah Lampung, 2025)
This study aims to analyze the influence of short videos on the actual purchasing behavior of young consumers in Semarang City. Using a quantitative approach, data were collected through questionnaires from 100 respondents exposed to a short video of the fictional product